(untitled) (Western European Journal of Historical Events and Social Science, 2025)
The article examines the sanctity of the family as the cornerstone of society, as well as the influence of social, economic, spiritual, and moral processes within the family on the upbringing of children. It is emphasized that marriage serves as the foundation of family stability and plays a crucial role in addressing demographic challenges